Combination of the MADM Model Yager and k-NN to Group Single Tuition Payments - Paliling, Alders; Sutoyo, Muh Nurtanzis (ILKOM Jurnal Ilmiah, 2023)
Tuition payments at State Universities (PTN) use a Single Tuition Fee (UKT) payment system. It has been  implemented to make it easier for students to pay their tuition. The UKT system is divided into several groups starting from the UKT group I  to VIII. Universitas Sembilanbelas November (USN) Kolaka  is a state university and the university should determine the amount of tuition fees for each student according to the UKT system. In determining the UKT group for each student, several variables were used to make it easier to group student into their UKT groups. However, the large number of students, a number of variables and the limited time to determine the amount of UKT for each student become an issue,  so a method was needed to help USN Kolaka in grouping UKT for each student. One thing that can be done was to use the MADM model Yager and k-NN in order to make it easier to group UKT students. The results of the study showed that the use of the MADM Model Yager and k-NN could determine the UKT group of the students, and the results obtained for the UKT group I were 63 people (21.95%), the UKT group II were 72 people (25.09%), the UKT group III were 120 people (41.81%), UKT group IV were 7 people (2.44%), and UKT group V were 25 people (8.71%).